2021
DOI: 10.1111/ijfs.15342
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment in the Serbian population and occurrence of histamine and heavy metals in fish and seafood

Abstract: The aim of this study was to conduct a quantitative exposure assessment of fish-borne histamine, cadmium, mercury and arsenic in the Serbian adult population. The consumption survey of fish/fishery products was administered to 1 000 respondents during 2018. Determination of histamine content was performed on 974 fish; cadmium on 1 909, mercury on 1 911 and arsenic on 1 891 fish and seafood samples during five years (2014)(2015)(2016)(2017)(2018). Monte Carlo analysis was used to estimate the intake of histamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…A significant impact of marine coastal pollution is metal-contaminated seafood, which has raised public attention due to its potential risks to human health [ 2 ]. Studies of PTMs in seafood have been increasing in the literature since the biomonitoring data are related to the human health risks of metal toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, many such biomonitoring studies with health risk assessments were reported from Pakistan [ 1 ], Thailand [ 2 ], Brazil [ 3 ], Serbia [ 4 ], China [ 5 , 19 , 21 , 24 ], Nigeria [ 6 , 25 ], Kuwait [ 8 ], Malaysia [ 9 , 26 ], Vietnam [ 11 ], Bosnia and Herzegovina [ 12 ], Romania [ 15 ], Serbia [ 16 ], Hungary [ 20 ] and Turkey [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant impact of marine coastal pollution is metal-contaminated seafood, which has raised public attention due to its potential risks to human health [ 2 ]. Studies of PTMs in seafood have been increasing in the literature since the biomonitoring data are related to the human health risks of metal toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, many such biomonitoring studies with health risk assessments were reported from Pakistan [ 1 ], Thailand [ 2 ], Brazil [ 3 ], Serbia [ 4 ], China [ 5 , 19 , 21 , 24 ], Nigeria [ 6 , 25 ], Kuwait [ 8 ], Malaysia [ 9 , 26 ], Vietnam [ 11 ], Bosnia and Herzegovina [ 12 ], Romania [ 15 ], Serbia [ 16 ], Hungary [ 20 ] and Turkey [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of PTMs in seafood have been increasing in the literature since the biomonitoring data are related to the human health risks of metal toxicity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. In particular, many such biomonitoring studies with health risk assessments were reported from Pakistan [ 1 ], Thailand [ 2 ], Brazil [ 3 ], Serbia [ 4 ], China [ 5 , 19 , 21 , 24 ], Nigeria [ 6 , 25 ], Kuwait [ 8 ], Malaysia [ 9 , 26 ], Vietnam [ 11 ], Bosnia and Herzegovina [ 12 ], Romania [ 15 ], Serbia [ 16 ], Hungary [ 20 ] and Turkey [ 22 ]. The six PTMs that were investigated in the present study were Cd, Cu, Fe, Ni, Pb and Zn because they are common anthropogenic metals and could potentially cause human health risks [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to their potential to bioaccumulate, the concentration of heavy metals in organisms located at higher trophic levels can reach concentrations that may be harmful to human health. Thus, the consumption of seafood in general and fish in particular is the main exposure route to heavy metals 9 11 . Exposure to heavy metals including lead (Pb), cadmium (Cd) and mercury (Hg) can lead to a number of adverse health effects, including a compromised renal and hepatic function 12 , teratogenic effects 13 15 , and cognitive impairments 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%